Penerapan Metode Pembelajaran PBL (Problem Based Learning) Terhadap Hasil Belajar Peserta Didik - Sakdiah Saily (STAIN Bengkalis, 2019)
This study aims to improve the implementation of Problem Based Learning (PBL) towards students’ achievement. Learning is part of education, which is supported by various elements of learning. Learning elements include objectives, learning materials, facilities or learning conditions, learning media, learning methods and evaluation methods. The problem that arises is that our education still dominated by knowledge as a fact must be memorized. On the other hand, there is the fact that teachers master the material but cannot carry out learning activities properly. This is based on a particular learning model. To overcome the problem, the implementation of problem based learning needed to implement. The effectiveness of this model is the students are more effective in thinking and understanding material. PBL model is one of the learning models where authentic assessment (real or concrete reasoning) can be applied comprehensively, in which there are elements of finding problems and solving (elements contained finding problems and problem solving).